Public-Private Dialogue in Fragile and Conflict-Affected Situations : Experiences and Lessons Learned - World Bank Group (World Bank, Washington, DC, 2016)
Public-private dialogue (PPD) is highly necessary in fragile and conflict-affected situations (FCS) to fill the gap resulting from the lack of legitimate institutions, to help create transparency and trust among stakeholders, and to identify the need for reforms and interventions that can improve the business environment and attract investment. Moreover, creating a platform for PPD can provide a useful starting point for private sector development in FCS for projects in key sectors, such as agribusiness and extractives, where PPD can help build links between large-scale investments and the local economy. To support PPD projects in FCS, the World Bank Group has conducted a survey of 27 task team leaders and other program staff members with experiences from 30 FCS countries. The survey was followed by in-depth interviews with 13 key staff members who have experience from selected countries. By conducting in-depth interviews, the Bank Group aimed to capture important experiences and lessons learned, including a description of challenges, useful tools and methods, and do s and don ts. The results of PPD are produced by the reforms it initiates and also the process it implements. In FCS, the peacebuilding and conflict-mitigating results are difficult to capture. However, the stakeholders that benefit from the results highly value them. This study will inform the design of guidelines intended for PPD project managers operating in FCS environments.